Prophetic Value-Based Islamic Education Outreach in Strengthening Family and Community Roles for Online Gambling Prevention - Maryono; Zaki Ulien Nuha; Rosan Mohamad Puji Santoso; La Ode Muhammad Butra Gueno Rere (ASSUNNAH PRESS, 2026)
The proliferation of online gambling in the digital era has generated significant social, economic, and psychological consequences, particularly with respect to family resilience and community social stability. These challenges demand community-based preventive efforts that optimise the potential of Islamic religious values as a form of social control. This community service programme aims to enhance public awareness of the hazards of online gambling and to strengthen the roles of the family and community in prevention efforts through an Islamic education approach grounded in Prophetic values (al-qiyam al-nabawiyyah). The programme partners comprise community leaders, the takmir of Masjid Al-Hidayah, students of the KUKERTA programme, and residents of Padukuhan Jelok, Kalurahan Pacarejo, Kabupaten Gunungkidul. Employing the Asset-Based Community Development (ABCD) approach across four stages — Discovery, Dream, Design, and Destiny — the programme was conducted on 29 January 2026 at Masjid Al-Hidayah using an educative-participatory method comprising interactive lectures and open discussion. Outcome indicators recorded measurable impacts: 82% of participants reported enhanced understanding of online gambling hazards; 17 discussion contributions were identified across five strategic themes; more than 90% of participants declared a commitment to strengthening family supervision and regular religious forums; and a mean satisfaction score of 4.4 out of 5 was achieved. These findings demonstrate that the integration of Prophetic values — amanah, shiddiq, tabligh, and fathanah — with asset-based community empowerment is effective in building collective awareness and strengthening the family as the primary bulwark of online gambling prevention